MORPHOLOGY OF THE AORTA IN METABOLIC SYNDROME - Khoshimov, B.L.; Akhmedova, S.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. In recent years, hypokinesia has become not only a medical but also a social problem. Several factorscause hypokinesia: high automation of production, transition to a sedentary lifestyle, and being in bed after certain diseases. The classification of hypokinesia is presented in several literature. According to the World Health Organization, about 60% of the world’s population does not have enough physical activity to lead a healthy lifestyle Methods. Mature white laboratory rats weighing 180-200 grams were used as study material. The white rats taken for the experiment were divided into 2 groups. Complex morphological studies include general histologic and histochemical techniques, morphometry, scanning electron microscopy, and transmission electron microscopy. Results. Studying the nature and initial changes of the morphological changes observed as a result of hypokinesia and the consequences of metabolic syndrome is an urgent medical problem. A high-calorie diet throughout life is considered one of the main causes of metabolic syndrome. In understanding the pathogenesis of metabolic syndrome and hypodynamia, it is important to know the morphological changes observed in these pathologies. As an object of research, we studied the morphological changes in arteries of elastic type. The obtained results revealed destructive and defragmentation changes in fibrous structures in the walls of elastic-type arteries. Conclusion. In experimental hypokinesia and metabolic syndrome, there is a thickening of the internal elastic membrane of the wall of the thoracic aorta, a decrease in the thickness of the middle layer, and a decrease in the number of smooth muscle cells in the vascular wall.